High sour natural gas dehydration treatment through low temperature technique: Process simulation, modeling and optimization - Rubaiee, Saeed (Chemosphere (Oxford), 2023)
Among the various fossil fuels, natural gas is a clean fuel because it has a less adverse impact on the environment compared to other energy sources. Natural gas emits less hazardous gases and less CO2 upon burning. Water, CO2, N2, H2S, and other contaminants could be present in raw natural gas, depending on its geographic location. The main issue among these contaminants is CO2, which decreases the calorific value of natural gas and corrodes pipes and process equipment. Absorption, adsorption, membrane separation, and cryogenic separation are the four main CO2 separation technologies. Cryogenic technologies for natural gas purification are environmentally friendly because they involve physical separation, and no harmful chemicals are required. Although cryogenic is an attractive alternative, it has some process limitations. The water must be removed before cryogenic separation because it can create piping blockage due to ice formation. The main goal is to remove water from natural gas at optimized conditions. The absorption technique employing triethylene glycol (TEG) as a solvent is the most widely used technology for dehydrating natural gas. Water extracts from natural gas as it passes over TEG, which acts as a dehydrating agent. The harmful effects of TEG on the environment are this technology's principal drawback. The current work investigates the dehydration of natural gas utilizing a low-temperature packed bed which could be an attractive alternative due to the absence of harmful chemicals. A thorough simulation analysis was carried out to learn more about the impact of the process parameter on the separation. The results showed that the pressure increase from 1 to 5 bar resulted in water removal from 25.4 to 83.7%. The optimum temperature and pressure for maximal water removal from natural gas were also determined. The maximum water was removed at 34 bar and −7.3 °C. [Display omitted] •A strategy for the simulation of natural gas dehydration was developed.•A model was developed to predict the percentage removal of water from natural gas.•The increase of pressure from 1 to 5 bar resulted in water removal from 25.4 to 83.7%.•The maximum water removal was obtained at 34 bar and −7.3 °C.